Analisis Rendahnya Minat Generasi Muda Bekerja di Sektor Pertanian di Desa Lendang Nangka Utara Kecamatan Masbagik Kabupaten Lombok Timur - Kholissatun Nawafi; Akhmad Jufri; Ali Akbar Hidayat (Masyarakat Ekonomi Syariah Bogor, 2026)
This study aims to analyze the factors that influence this low interest of young people in working in the agricultural sector in Lendang Nangka Utara Village, Masbagik District, East Lombok Regency. This study uses a qualitative approach. There are three paths of qualitative data analysis, namely data reduction, data presentation, and conclusion drawing. With data obtained through interviews, observations, and documentation with triangulation source validity testing. The research informants consisted of young people, hamlet heads, village secretaries, and the patrents of the interviewed youth.The results of the study show that the interest of the younger generation in Lendang Nangka Utara Village in the agricultural sector is relatively low. This low interest is influenced by several key factors: wages/income, continuity, education, family land assets, and family environment. Government support is needed in the form of training, capital, and modern technology to increase the interest of the younger generation in the agricultural sector.